2002
DOI: 10.1021/cm010930x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Characterization and Properties of Completely Saturated Quaternary Phosphonium Salts. Ordered, Room-Temperature Ionic Liquids

Abstract: The properties of four completely saturated and one partially saturated salts consisting of methyl-tri-n-decylphosphonium cations and either chloride, chloride monohydrate, bromide, bromide monohydrate, or nitrate anions are reported. Their neat phase behavior has been examined by polarizing optical microscopy, differential scanning calorimetry, and X-ray diffraction. The monohydrates form smectic phases that persist in >90 °C ranges and extend from below room temperature; they are ordered, room-temperature io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 57 publications
1
59
0
Order By: Relevance
“…[14,15] Moreover, Weiss et al have reported similar solid structures for various long alkyl-chain phosphonium RTILs, many of which melt into a liquid-crystalline phase in which much of this order is maintained. [16][17][18] Where studied, this liquid-crystalline structure was largely unaffected by the addition of up to 20 wt % of a small organic molecule (acetonitrile). [17] If the solute was disrupting the ion-ion interactions, the structure would probably be destroyed, suggesting that the added acetonitrile primarily occupies the alkyl region.…”
Section: à11mentioning
confidence: 99%
“…[14,15] Moreover, Weiss et al have reported similar solid structures for various long alkyl-chain phosphonium RTILs, many of which melt into a liquid-crystalline phase in which much of this order is maintained. [16][17][18] Where studied, this liquid-crystalline structure was largely unaffected by the addition of up to 20 wt % of a small organic molecule (acetonitrile). [17] If the solute was disrupting the ion-ion interactions, the structure would probably be destroyed, suggesting that the added acetonitrile primarily occupies the alkyl region.…”
Section: à11mentioning
confidence: 99%
“…[10][11][12] Different types of ionic liquid crystals have been investigated, among others imidazolium, [13][14][15][16][17][18] pyridinium, [13,16,[19][20][21][22] quaternary ammonium [2][3][4]23] and quaternary phosphonium salts. [24,25] Recently, we reported on nematic ionic liquid crystals and a luminescent tetrakis b-diketonate lanthanidome-A C H T U N G T R E N N U N G sogen with mesogenic imidazolium cations. [26] The liquidcrystalline behaviour of the ionic salts strongly depends on the nature of both the cation and the anion, but also on the length of the alkyl chain of the organic cation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of attempts to quantify the solvent properties of ILs using solvatochromic dyes [8][9][10][11][12][13][14][15][16][17][18], linear free energy relationships (LFER) [19,20], partitioning studies [21], and other approaches [22,23]. Although a range of solvent properties has been reported, there is a general consensus that ILs have polarities comparable to polar aprotic solvents, such as DMF and acetonitrile, or protic solvents, such as short-chain alcohols.…”
Section: Introductionmentioning
confidence: 99%